Melatonin enhances arsenic trioxide-induced cytotoxicity by modulating autophagy in an acute promyelocytic leukemia cell line - Wei, Xia; Pu, Xin; Yang, Sainan; Meng, Xiaoqin; Chen, Xue; Zhang, Zhihua; Sheng, Xaomin; Xiang, Dan; Zhang, Yong (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Arsenic trioxide (ATO)-containing therapeutic strategies are widely used in the treatment of acute promyelocytic leukemia (APL). Growing evidence has shown that melatonin enhances the radio- or chemo-sensitivity of numerous cancer cells. However, whether melatonin is capable of enhancing the cytotoxic effects of ATO in APL cells remains unknown. Methods: The present study conducted a 24 h melatonin exposure followed by additional 12, 24 or 48 h ATO exposure in the APL cell line NB4 with or without autophagy-related protein 7 (ATG7) silencing by RNA interference. Cell cytotoxicity was evaluated by Cell Counting Kit-8 (CCK-8) and lactate dehydrogenase (LDH) assays. Cell apoptosis was assessed by Annexin-V/propidium iodide assay and western blotting against cleaved caspase 3, Bax and Bcl-2. Autophagy was evaluated by western blotting against LC3. Results: Pre-treatment with a non-cytotoxic dose of melatonin significantly enhanced ATO-mediated reduced cell viability and increased LDH release. Furthermore, melatonin pre-treatment also enhanced ATO-mediated increase in early and late apoptosis, as well as the expression of Bax and cleaved caspase 3, while further decreasing ATO-mediated reduced expression of Bcl-2. Concomitantly, melatonin pre-treatment increased LC3II expression and enhanced the ATO-mediated elevation in LC3II expression. However, autophagy inhibition by ATG7 silencing blocked the enhancing effects of melatonin on ATO-induced apoptosis and cytotoxicity. These findings indicated that melatonin pre-treatment enhances ATO-induced cytotoxicity by modulating ATG7-mediated autophagy. Conclusions: Melatonin could represent a valuable adjuvant to ATO in APL treatment, particularly in patients with ATO-resistant APL.